Do elderly choose nursing homes by quality, price or location? - Magdalena Stroka; Hendrik Schmitz (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
Quality report cards addressing information asymmetry in the health care market have become a popular strategy used by policymakers to improve the quality of care for elderly. Using individual level data from the largest German sickness fund merged with institutional level data, we examine the relationship between nursing home quality, as measured by recently introduced report cards, nursing home prices, nursing home s location and the individual choice of nursing homes. Report cards were stepwise introduced as of 2009 and we use a sample of 2010 that includes both homes that had been evaluated at that time and that had not yet been. Thus, we can distinguish between institutions with good and bad ratings as well as non-rated nursing homes. We find that the probability of choosing a nursing home decreases in distance and price. However, we find no significant effect of reported quality on individuals choice of nursing homes.
Keywords: I10; I11; I19; 330